Penyuluhan garam beryodium terhadap perubahan pengetahuan ibu rumah tangga dalam penggunaan garam yodium - Nurhayati Nurhayati; Irwan Irwan; Ampera Miko (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Disorders Due to Iodine Deficiency (IDD) is one of the main nutritional problems that cannot be eliminated due to an environment that is poor in iodine sources. Residents who live in areas with an iodine deficit and only consume available food and drink. Lack of knowledge about the causes of IDD is the driving force for the high incidence of health problems.Objectives: This study aims to determine whether there is an effect before and after the counseling is carried out on changes in the knowledge of housewives and the use of iodized salt.Methods: This type of research is a quasi-experimental research with pre-test and post-test. This research was conducted in Trienggadeng District, Pidie Jaya Regency, which was conducted in 2019. The sample size in this study was the entire population as a sample, namely all 39 housewives. Data collection includes primary data and maternal data. Data processing in this study with 4 stages, including stages namely; editing, coding, entry, processing, and cleaning data. Data analysis was carried out univariate and bivariate. The statistical test for bivariate analysis was using the T-dependent statistical test.Results: The results showed that the level of knowledge and use of iodized salt in housewives in Trienggadeng District, Pidie Jaya Regency. There is an effect of counseling the benefits of iodized salt before and after on increasing the knowledge of housewives, with a value of p = 0.001 (p < 0.05). There is an effect of counseling the benefits of iodized salt between before and after the use of iodized salt to housewives, with a value of p = 0.000 (p < 0.05). Conclusion: There is the influence of education on the benefits of iodized salt to increase knowledge of housewives, but it is also significant in household use.